Progress to proficiency : - Jones, Leo (Cambridge Univ. Press, 1986)
This popular course combines systematic preparation for all five papers of the Proficiency exam with a fresh and lively approach. The new course retains the skills sections, comprehensive vocabulary and communication activities that made the original editions so popular. In addition it is packed with new and absorbing texts and original interviews with interesting personalities. The course is also available as a self-study edition which provides answers to the tasks, explanations, model answers and exam tips.